2008
DOI: 10.1186/gb-2008-9-10-r146
|View full text |Cite
|
Sign up to set email alerts
|

A genome wide analysis of the response to uncapped telomeres in budding yeast reveals a novel role for the NAD+ biosynthetic gene BNA2 in chromosome end protection

Abstract: NAD+ metabolism may be linked to telomere end protection in yeast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…4J)(8). Previous studies showed that defects in kyurenine biosynthesis suppressed cdc13-1 TS mutants, suggesting that elevated NAD+ levels inhibit telomere capping (23). Thus, the global genetic interaction network traced novel functional connections whereby defects in MTC pathway-dependent protein trafficking alter aromatic amino acid homeostasis, which appears to modulate steady state levels of kyurenine biosynthetic pathway metabolites, linking cell polarity to telomere capping through altered NAD+ levels.…”
Section: Predicting Novel Gene Functionmentioning
confidence: 99%
“…4J)(8). Previous studies showed that defects in kyurenine biosynthesis suppressed cdc13-1 TS mutants, suggesting that elevated NAD+ levels inhibit telomere capping (23). Thus, the global genetic interaction network traced novel functional connections whereby defects in MTC pathway-dependent protein trafficking alter aromatic amino acid homeostasis, which appears to modulate steady state levels of kyurenine biosynthetic pathway metabolites, linking cell polarity to telomere capping through altered NAD+ levels.…”
Section: Predicting Novel Gene Functionmentioning
confidence: 99%
“…Additionally, independent genome-wide screens for deletion mutants showing genetic interactions with the cdc13-1 mutation had been performed [30], [31]. Ranking the screened genes on the basis of their temporal gene expression revealed that the genes with the highest DCeN values were enriched with genetic interactions with cdc13-1 (permutation test, most significant p  = 0.014; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…cruzi , suggesting that GAPDH can sense the redox state, which subsequently controls whether it associates with telomeric DNA. The involvement of NAD + in a chromosomal end protection mechanism was also observed in yeast [ 35 ]. Our data also suggests that treatment with exogenous NAD + trigger translocation of GAPDH to nucleolus.…”
Section: Discussionmentioning
confidence: 96%